2005
DOI: 10.1267/ahc.38.295
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of MUC Mucin Core Protein in the Intrahepatic Biliary System: Physiological Distribution and Pathological Significance

Abstract: Mucin secreted by mucosal epithelial cells plays a role in the protection of the mucosal surface and also is involved in pathological processes. So far, MUC1-4, 5AC, 5B, 6-8, 11-13 and 15-17 genes coding the backbone mucin core protein have been identified in humans. Their diverse physiological distribution and pathological alterations have been reported. We have studied the expression profiles of MUC genes in the intrahepatic biliary system in developmental, normal and diseased livers using immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The distribution of MUC2 and CDX2 expression is similar to that in previous reports in that MUC2 expression is restricted to the cytoplasm of goblet type cells and CDX2 is expressed extensively compared with MUC2. 1,8,17 CDX2 expression may be an early event in intestinal metaplasia because the expression of MUC2 is found within BECs that express CDX2. The extensive expression of CDX2 might suggest that CDX2 exists upstream in the pathogenesis of intestinal metaplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of MUC2 and CDX2 expression is similar to that in previous reports in that MUC2 expression is restricted to the cytoplasm of goblet type cells and CDX2 is expressed extensively compared with MUC2. 1,8,17 CDX2 expression may be an early event in intestinal metaplasia because the expression of MUC2 is found within BECs that express CDX2. The extensive expression of CDX2 might suggest that CDX2 exists upstream in the pathogenesis of intestinal metaplasia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in chronic cholangitis such as hepatolithiasis, intestinal metaplasia with goblet cells occurs, and MUC2 is aberrantly expressed in goblet cells colocalized with CDX2. 1,[10][11][12][13][14][15][16][17][18] Bacterial infections are implicated in chronic cholangitis with intestinal metaplasia. 19,20 Lipopolysaccharide (LPS), a bacterial component, is known to cause MUC2 overexpression in cultured biliary epithelial cells (BECs).…”
mentioning
confidence: 99%
“…Mucins are high molecular weight glycoproteins with oligosaccharides attached to serine or threonine residues of the mucin core protein backbone by O ‐glycosidic linkages, which are produced by various epithelial cells. Core proteins for human mucins (MUC1‐MUC9, MUC11–13, MUC15–20) have been identified recently . Mucins are categorized into membrane‐associated mucins (MUC1, MUC3 MUC4, MUC12, MUC16, and MUC17), gel‐forming mucins (MUC2, MUC5AC, MUC5B, and MUC6), and soluble mucin (MUC7) …”
Section: Introductionmentioning
confidence: 99%
“…Core proteins for human mucins (MUC1-MUC9, MUC11-13, MUC15-20) have been identifi ed recently. [2][3][4][5][6][7][8][9][10][11][12][13] Mucins are categorized into membraneassociated mucins (MUC1, MUC3 MUC4, MUC12, MUC16, and MUC17), gel-forming mucins (MUC2, MUC5AC, MUC5B, and MUC6), and soluble mucin (MUC7). 14 Our series of immunohistochemical studies for mucin expression in various human tumors, including pancreatic tumors, have demonstrated that the expression of MUC1 mucin (membrane mucin) is related to an invasive proliferation of tumors and/or a poor outcome for the patient.…”
mentioning
confidence: 99%
“…Intestinal metaplasia showing goblet cells, Paneth cells, and endocrine cells, is known to occur in non‐neoplastic and neoplastic conditions in extra‐intestinal organs, such as the pancreas, stomach, and esophagus 1–4 . Intestinal metaplasia, particularly goblet cell metaplasia, is also known to develop in the diseased biliary tree in chronic cholangitis, such as hepatolithiasis 5–7 …”
Section: Introductionmentioning
confidence: 99%